BIMBINGAN TEMAN SEBAYA TENTANG PENYESUAIAN DIRI PESERTA DIDIK KELAS X SMAN 9 PONTIANAK - Rofiqoh, Khofidatur; Wicaksono, Luhur; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe peer of counseling is a ministration process by fellow between one self and another in processing the adjustment. In this research, adjustment means students? processes to adapt themselves in entering the new surrounding, whether it is about friends, teachers, or school environtment. In order to help the students in getting to understand themselves, it is needed to be solved so the peer counseling is able to give its counsils to get the adjusment in the new surrounding. Therefore, the researcher wants to know deeper regarding the peer of counseling towards the adjusments of year-10 students at SMAN 9 Pontianak. The research probelm was ?how does the peer of counseling regarding students? adjustments to the year-10 students at SMAN 9 Pontianak??. This research aimed to know how the peer of counseling regarding students? adjustments to the year-10 students at SMAN 9 Pontianak. The method of this research was descriptive study in form of survey study research. The sample of this research were 38 of year-10 students at SMAN 9 Pontianak. This research used quantitative approach. The technique of data collection indirect communication with questionnaire as the data collection. Meanwhile, the technique of data analysis the researcher used percentage calculation. Based on the data analysis, the peer of counseling regarding students? adjusments to the year-10 students at SMAN 9 Pontianak significantly passed and as categorized as ?Good?.Keywords: Peer, Adjustments